Temporal variation of the microplastic concentration in a stream that receives discharge from wastewater treatment plants - Montecinos Espinoza, Susana de Los Angeles (2023)
The temporal variation of the microplastic concentration was studied in the Langueyú stream, which is located in the department of Tandil, in the southeast of the Buenos Aires province in Argentina. This stream receives discharge from the wastewater treatment plants from a medium-sized city. A quantitative analysis of the microplastic concentration was carried out in different samplings, corresponding to different seasons. The study focused on the most contaminated point, located after the discharge of effluents from plants. Higher concentrations of MPs were found in winter (dry season), having approximately 6 times the concentrations found in summer and autumn (wet seasons). However, these differences would not be a direct consequence of the amount precipitation, but rather would be associated with a seasonal variation of human activities, mainly with respect to the type of clothing used in the cold season. The microfibers correspond to around 60?90% of microplastics found. The discharge from the plants causes changes in the parameters of the stream water, such as high electrical conductivity values, and also provide metallic contaminants such as Ca, Zn, and in smaller amounts Pb, Fe, Ni and Cu, which were found adhered to the microplastics and remain in the stream water in high quantities 3 km after the study point. The microplastic concentration presents a linear empirical correlation with the conductivity, and it was found that conductivity measurements would serve as an indicator of the microplastic concentration in the system under study.